Including a Symposium on 50 Years of the Union for Radical Political Economics - Fiorito, Luca (Research in the History of Economic Thought and Methodology Ser., 2019)
Volume 37A of Research in the History of Economic Thought and Methodologyfeatures a symposium celebrating 50 years of the Union of Radical Political Economics, and includes an archival contribution from the papers of Alvin Hansen, reflecting on the influence and contributions of John R. Commons.